2018
DOI: 10.3389/fnmol.2018.00332
|View full text |Cite
|
Sign up to set email alerts
|

Negative Evidence for a Functional Role of Neuronal DNMT3a in Persistent Pain

Abstract: Traditionally, neuroscience has had to rely on mixed tissue analysis to examine transcriptional and epigenetic changes in the context of nervous system function or pathology. However, particularly when studying chronic pain conditions, this approach can be flawed, since it neglects to take into account the shifting contribution of different cell types across experimental conditions. Here, we demonstrate this using the example of DNA methyltransferases (DNMTs) – a group of epigenetic modifiers consisting of Dnm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
(50 reference statements)
1
13
0
Order By: Relevance
“…A recent study performed using sensory neuron-specific Dnmt3a knockout mice provided evidence against a role for Dnmt3a expression in dorsal root ganglia neurons in nociception. 34 These findings, in combination with our study – based instead on manipulation of the expression of Dnmt3a2 in the dorsal horn of the spinal cord – suggest that Dnmt3a2 contributes differentially to long-lasting hypersensitivity depending on the affected area.…”
Section: Discussionsupporting
confidence: 65%
“…A recent study performed using sensory neuron-specific Dnmt3a knockout mice provided evidence against a role for Dnmt3a expression in dorsal root ganglia neurons in nociception. 34 These findings, in combination with our study – based instead on manipulation of the expression of Dnmt3a2 in the dorsal horn of the spinal cord – suggest that Dnmt3a2 contributes differentially to long-lasting hypersensitivity depending on the affected area.…”
Section: Discussionsupporting
confidence: 65%
“… 9 Interestingly, the role of DNMT3a in persistent pain remains controversial. 5 , 7 , 8 , 35 , 36 All of these factors prompted us to test whether DNMT3a-produced DNA methylation is involved in alteration of the 4 candidate genes above. Considering that 5-Aza-dC inhibits all known DNMTs, and DNMT3a-specific or isoform-specific inhibitors are still under development, 37 , 38 we addressed this question by overexpressing DNMT3a.…”
Section: Resultsmentioning
confidence: 99%
“…A series of studies from a lab showed that restoring global DNMT expression levels within a tissue following a nerve injury is sufficient to alter pain responses, 6 - 8 although the functional role of DNMT3a in mouse sensory neurons in persistent pain has recently been challenged. 36 Given that DNMTs could alter a multitude of genes that are either pro-nociceptive or anti-nociceptive, that DNMT expression levels are sensitive to changing tissue environments, and that DNMT is only one of many families enzymes involved in gene transcription, additional studies are warranted to confirm whether global changes in DNMT expression levels bear any functional relevance in pain modulation.…”
Section: Discussionmentioning
confidence: 99%
“…Brain, behavior, and immunity, 68, pp.248-260. Tanga, F.Y., Raghavendra, V. and DeLeo, J.A., 2004 TrpV1, which is well expressed in nociceptive neurons; Dnmt3a which is very lowly expressed if at all in neurons (Saunders et al, 2018); Nav1.8; CD40, a myeloid cell marker;…”
Section: Discussionmentioning
confidence: 99%
“…Calca, one of the most highly expressed genes in DRG; TrpV1 and Nav1.8, which are well expressed in nociceptive neurons; and Dnmt3a, which is very lowly expressed (Saunders et al, 2018). It is evident the two transcripts coding for the receptor chains of the GM-CSF receptor, namely CSF2Rα and CSF2Rβ, are expressed at levels below our negative control transcript in the DRG -the CSF2Rβ gene, in particular, appears to be undetectable, even by a technique as sensitive as RNA-seq.…”
Section: Gm-csf Does Not Modulate Gene Expression In Purified Neuronsmentioning
confidence: 99%